Extraction of castor seed oil and study its quality at Ain Shaqqaq site in the Syrian coast - وفاء غندور; نوال حمدكو (Latakia University Journal -Biological Sciences Series, 2022)
The oil was extracted by using Soxhlet apparatus using the organic solvent acetone from castor bean seeds Ricinus communis, L., the plant belongs to the Euphorbiaceae family in temperate regions and subtropics, identifying the fatty acids was done by gas chrmatography technique associated with the mass spectrometry GC/ MS. The results showed that the percentage of oil extracted from the seeds was (46%) in the studied site. The results of the analysis also showed that the oil contains (5) compounds, which constituted 100% of the total oil. It was found that the ricinoleic acid is the main component of the oil with a percentage of (71.57%), while the other fatty acids present are linoleic (10.75%), oleic (11.40%), Stearic (2.66%), palmitic (3.62%) respectively, and the percentage of unsaturated fatty acids (UFA) reached (93.72%) of the total fat.